Important blood pressure changes in clinical practice: narrative literature review - Maria Cristina PEDRAZINI; Luciane Francischini Gottschall ODONE; Mônica Feresini GROPPO; Francisco Carlos GROPPO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT The aim of this study was to emphasize the importance of monitoring vital signs, especially blood pressure, during dental care. Through a narrative review, the changes in blood pressure that may occur during outpatient procedures and the measures to be taken were discussed. The available literature was consulted in databases (PubMed, Scielo, Web of Science and Google Scholar), complemented by the analysis of the bibliographic references included and updated until April 2021. The keywords were used: "Anamnesis", "Arterial Pressure", "Arterial Hypertension", "Hypertensive Crisis", "Risk factors", "Stroke", "Subclavian Theft Syndrome" and "Atherosclerosis". It was concluded that care should be applied to all patients, but mainly to those over 50, hypertensive or not, with hypercholesterolemia, diabetes, anxious and fearful. All vital signs must be monitored, including the pain score. The situations of anxiety, pain and fear are triggers for changes in blood pressure even in normotensive patients as in controlled hypertensive patients. The blood pressure measurement, in the first consultation, must be performed in both arms and repeated annually or whenever there is a change in the patient's health status. In all other consultations, blood pressure control, as well as the assessment of all vital signs, must be performed before, during, after the procedure and before discharge. In the face of any major change, it is necessary to assess the risk/benefit ratio of the continuity of the procedure, so that risks to patients are avoided or minimized, as well as for the necessary referrals to be made.